The Muteness of Dogs: Pablo Larraín's El club (2015). Issue 1 (2nd January 2017) - Wright, Sarah
Abstract: This paper reflects on films from the recent boom in Chilean filmmaking in which animals, specifically, dogs, are called upon to articulate what is unsayable or ungrievable. In films such as Fernando Guzzoni's Carne de perro (2012), Sebastián Sepúlveda's Las niñas Quispe (2013) and Pablo Larraín's El Club (2015), the death of a dog articulates biopolitical regimes, human rights abuses and child abuse. This paper will focus on Larraín's El Club, a film which deals with the silences and cover-ups of the Catholic Church in Chile over human rights and child abuses. With recourse to Alice Kuzniar's moving portrait of human-canine relations in her book Melancholia's Dog, I will explore the fleeting projections and shifting inter-subjective embodiments occasioned by the dog in this film as well as the extent to which the dog gestures towards a state of melancholia which captures the psychic pain at large in the Chilean panorama. I will turn to Jacques Derrida (in particular, his relationship with his cat) on the relationship between human and non-human animals, in order to explore further the ways in which the nonhuman animal in this film (a greyhound), functions as allegory, projection or anthropomorphization of human concerns as well as the extent to which the dog's suffering can be seen on its own terms.